2020
DOI: 10.3389/fpsyg.2020.00093
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence, Belongingness, and Mental Health in College Students

Abstract: Mental health problems are prevalent amongst today's college students and psychosocial stress has been identified as a strong contributing factor. Conversely, research has documented that emotional intelligence (EQ) is a protective factor for depression, anxiety and stress (mental health problems). However, the underlying mechanism whereby EQ may support stronger mental health is currently not well understood. This study used regression analyses to examine the hypothesis that belongingness (inclusion, rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
71
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 36 publications
5
71
0
5
Order By: Relevance
“…However, their results did not confirm the impact of students' housing conditions on anxiety. Besides, Moeller et al ( 2020 ) found out that belongingness partially mediated the association between emotional intelligence and adaptation in a sample of US undergraduate students. Students with stronger emotional intelligence showed higher levels of belongingness which, in turn, was associated with better overall mental health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, their results did not confirm the impact of students' housing conditions on anxiety. Besides, Moeller et al ( 2020 ) found out that belongingness partially mediated the association between emotional intelligence and adaptation in a sample of US undergraduate students. Students with stronger emotional intelligence showed higher levels of belongingness which, in turn, was associated with better overall mental health.…”
mentioning
confidence: 99%
“…These results underline that it is of fundamental importance to adopt an integrated approach toward university students' psychological distress. Franzoi et al suggested the need to develop preventative and therapeutic interventions tailored to students' clinical characteristics, Moeller et al ( 2020 ) suggested to target interventions to students experiencing greater feelings of rejection or isolation, while Navarro-Mateu et al suggested the promotion of measures and intervention programs aimed at improving students' quality of life, and Backhaus et al suggested the implementation of on-campus mental health counseling services and interventions focused on enhancing social capital. Moreover, Karyotaki et al suggested that up to 46.9–80.0% of 12-month disorder prevalence might be eliminated if stress prevention interventions were developed.…”
mentioning
confidence: 99%
“…Several studies have shown perceptions of loneliness to be associated with negative mental health and health outcomes, poorer life satisfaction, and more negative coping strategies [14][15][16]. A lack of social bonds and social exclusion, related to loneliness, have also been shown to contribute to anxiety; and conversely, possessing a sense of belonging is strongly associated with happiness and subjective wellbeing [17][18][19]. Studies of students also demonstrate that having a sense of belonging is associated with reduced loneliness, social anxiety, and depression, suggesting that it may be a protective factor for mental health among post-secondary students [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, their results did not confirm the impact of students' housing conditions on anxiety. Besides, Moeller et al (2020) found out that belongingness partially mediated the association between emotional intelligence and adaptation in a sample of US undergraduate students. Students with stronger emotional intelligence showed higher levels of belongingness which, in turn, was associated with better overall mental health.…”
mentioning
confidence: 96%
“…These results underline that it is of fundamental importance to adopt an integrated approach toward university students' psychological distress. Franzoi et al suggested the need to develop preventative and therapeutic interventions tailored to students' clinical characteristics, Moeller et al (2020) Their results showed that students started treating themselves better in their everyday life. They became more supportive and friendlier toward themselves, as well as more aware of how harshly they treated themselves in difficult situations.…”
mentioning
confidence: 99%